المحاسبة الاجتماعية: مدخل لدراسة التدقيق الأجتماعي - امين, ساكار ظاهر عمر; عزیز, هێمن محمد; سعید, یعقوب أحمد حمە (Sulaimani Journal for Humanities, 2021)
This study examines social responsibility accounting, as an introduction to social auditing in firms operating in the Kurdistan Region-Iraq. This study aims to measure the perception of firms’ management in the Region towards social responsibility concept and to demonstrate the need for companies in the Region to implement the concept of social responsibility accounting. Moreover, the study attempts to highlight the potential of the external auditor in addressing the sources of pollution and waste and implementing preventive actions with their regard. In order to achieve the objectives, a questionnaire form, consists of 30 questions, was constructed and distributed to the targeted respondents including general managers, heads of segments, specifically the accounting and auditing units). The collected data were analyzed using (SPSS 22.0) through statistical methods and regression analysis. The findings of the study show that the general economic resources that companies consume in its operational activity, such as water and air, are not free goods, but rather economic and social resources. Furthermore, companies need to compensate society for what they consume from these resources. Social audit also contributes to the management’s rationalization processes and the organization leadership in coordination with its strategic goals. The study, therefore, recommends companies to compensate society for the natural resources that they consume because the ownership of these resources is society as whole. Additionally, companies need to set up a system to preserve the environment and protect it from damages caused by their operational activities.
Keywords: Social Responsibility Accounting; Social Auditing; Environment; Kurdistan Region